The Link between Type III Reg and STAT3-Associated Cytokines in Inflamed Colonic Tissues - Xu, Xin; Fukui, Hirokazu; Ran, Ying; Wang, Xuan; Inoue, Yoshihito; Ebisudani, Nobuhiko; Nishimura, Heihachiro; Tomita, Toshihiko; Oshima, Tadayuki; Watari, Jiro; Kiyama, Hiroshi; Miwa, Hiroto (Mediators of Inflammation, 2019)
Reg (regenerating gene) family proteins are known to be overexpressed in gastrointestinal (GI) tissues under conditions of inflammation. However, the pathophysiological significance of Reg family protein overexpression and its regulation is still unclear. In the present study, we investigated the profile of Reg family gene expression in a colitis model and focused on the regulation of Reg IIIβ and IIIγ, which are overexpressed in inflamed colonic mucosa. C57BL/6 mice were administered 2% dextran sulfate sodium (DSS) in drinking water for five days, and their colonic tissues were investigated histopathologically at interval for up to 12 weeks. Gene expression of the Reg family and cytokines (IL-6, IL-17, and IL-22) was evaluated by real-time RT-PCR, and Reg IIIβ/γ expression was examined by immunohistochemistry. The effects of cytokines on STAT3 phosphorylation and HIP/PAP (type III REG) expression in Caco2 and HCT116 cells were examined by Western blot analysis. Among Reg family genes, Reg IIIβ and IIIγ were alternatively overexpressed in the colonic tissues of mice with DSS-induced colitis. The expression of STAT3-associated cytokines (IL-6, IL-17, and IL-22) was also significantly increased in those tissues, being significantly correlated with that of Reg IIIβ/γ. STAT3 phosphorylation and HIP/PAP expression were significantly enhanced in Caco2 cells upon stimulation with IL-6, IL-17, and IL-22. In HCT116 cells, those enhancements were also observed by IL-6 and IL-22 stimulations but not IL-17. The link between type III Reg and STAT3-associated cytokines appears to play a pivotal role in the pathophysiology of DSS-induced colitis.